ESTETIKA VIRTUAL DALAM GAME 3D “DREADEYE VR”: (PENDEKATAN MDA FRAMEWORK) - Misky, Fatma; Widyananda Putra, Ricky (Universitas Budi Luhur, 2022)
Indonesia is very rich in myths that exist in society, the wealth of myths found in the archipelago is illustrated by the many community stories that are still found today. One example is the myth about Indonesian ghosts and their various frightening forms. Fear arises from human ignorance of something and develops into a wild fantasy in humans, until finally it can be accepted by human logic. This can be seen from the many kinds of entertainment media that take the theme of horror, one of the media currently used is video games. One of the games from Indonesia that has developed this virtual aesthetic using 3D visualization technology is the game studio Digital Happines from Bandung, with the game title Dreadeye VR. This game is a Virtual reality game where to play it requires a VR device. With the concept of Virtual reality, this game provides deeper interactivity for users to explore real spaces in the virtual world. Virtual reality brings a new experience for users to continue to enjoy objects in the game, even if they do not make direct contact. This can lead to being carried away to bring new meaning to each individual. So the problem of this research is, how the Dreadeye VR game presents virtual aesthetics for the players and the purpose of this research is to find out the factors that form virtual aesthetics in the Dreadeye VR game. The methodology of this research is qualitative, while the approach and theory used is MDA (Mechanic, Dynamic, Aesthetic), the MDA approach describes each interrelated component such as mechanics, dynamics, and aesthetics. Mechanics explain programming and game rules, dynamics describe interactive games and playing experiences, aesthetics describe the sensations felt when interacting with games.